Mixed-reality Automotive Testing with SENSORIS - Varga, Balázs; Szalai, Mátyás; Fehér, Árpád; Aradi, Szilárd; Tettamanti, Tamás (Periodica Polytechnica Transportation Engineering, 2020)
Highly automated and autonomous vehicles become more and more widespread changing the classical way of testing and validation. Traditionally, the automotive industry has pursued testing rather in real-world or in pure virtual simulation environments. As a new possibility, mixed-reality testing has also appeared enabling an efficient combination of real and simulated elements of testing. Furthermore, vehicles from different OEMs will have a common interface to communicate with a test system. The paper presents a mixed-reality test framework for visualizing perception sensor feeds real-time in the Unity 3D game engine. Thereby, the digital twin of the tested vehicle and its environment are realized in the simulation. The communication between the sensors of the tested vehicle and the central computer running the test is realized via the standard SENSORIS interface. The paper outlines the hardware and software requirements towards such a system in detail. To show the viability of the system a vehicle in the loop test has been carried out.